Influence of de novo donor-specific antibody on early renal allograft function recovery. (20th February 2015) - Zheng, Jin; Xue, Wujun; Jing, Xin; Hou, Jun; Tian, Xiaohui; Tian, Puxun; Ding, Xiaoming; Pan, Xiaoming; Yan, Hang; Feng, Xinshun; Xiang, Heli; Li, Yang; et al.
Abstract: Background : The aim of the present study is to investigate the impact of de novo donor-specific antibodies (dnDSA) on early graft function, to provide objective reference for early clinical diagnosis and reasonable individualized treatment. Methods : 305 cases of renal transplant patients for the first time were observed in this study. Follow-up time for all recipients was 6 months after operation. HLA antibody, DSA, renal function were monitored after transplant. Results : In total of 305 cases, 66 cases (21.64%) were HLA antibody positive and 21 cases (6.89%) showed acute rejection (AR) in 6 months after transplant. The HLA antibody-positive patients included six cases of dnDSA-positive and 60 cases of dnDSA-negative. The incidence of AR was 2.09% (5/239) in HLA antibody-negative patients, 18.33% (11/60) in HLA antibody positive with DSA-negative patients, and 83.33% (5/6) in HLA antibody-positive patients with DSA-positive. There was a big difference between DSA-negative and DSA-positive patients ( p < 0.01). The recovery time of AR patients with DSA-positive were longer than DSA-negative patients, and the recovery graft function of AR patient with DSA-positive were not as good as those with DSA-negative. Conclusions : The appearance of dnDSA in the early stage of kidney transplantation is a warning sign of AR occurrence. Dynamic monitoring of HLA antibody and DSA could predict the state of graft function, and play an important role in the prevention of AR, timely and effectively.